2007
DOI: 10.15376/biores.2.4.789-811
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on cracking and mechanical properties of wood during wood drying - A review

Abstract: The occurrence of cracks and loss of mechanical properties are major problems in wood drying, and careful control of drying conditions is necessary in order to avoid this form of defects. Wood drying at different temperatures, especially high temperatures, has gained much interest in the last several decades. Some solutions for minimizing drying defects, such as cracks and decrease of mechanical properties due to the increase of drying rates, decrease of drying time and thus cost, must be acknowledged and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Drying stresses are the internal stresses in the process of wood drying, and acting as a mutual restriction within the internal tissues of the wood. It is closely related to internal factors such as the wood component, material properties, and moisture content, as well as external environmental factors such as drying temperature and relative humidity [ 12 , 13 , 14 , 15 ]. Generally, in the early stage of drying, the drying stresses are small and will not damage the wood.…”
Section: Introductionmentioning
confidence: 99%
“…Drying stresses are the internal stresses in the process of wood drying, and acting as a mutual restriction within the internal tissues of the wood. It is closely related to internal factors such as the wood component, material properties, and moisture content, as well as external environmental factors such as drying temperature and relative humidity [ 12 , 13 , 14 , 15 ]. Generally, in the early stage of drying, the drying stresses are small and will not damage the wood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated an increase in gas permeability in solid wood specimens as a result of high temperatures and below zero temperatures; the extreme hot/cold conditions resulted in micro-checks in specimens, facilitating the transfer of fluids in them (Taghiyari 2012). In this connection, it was previously argued that thermal modification creates some spaces in solid wood, like cracking (Oltean et al 2007;Bastani et al 2015Bastani et al , 2016b; these extra spaces provides new pathways for different fluid to penetrate and pass through. Both sapwood and heartwood specimens showed the same weight losses (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…This means that any reduction or destruction in hemicelluloses structure of the cell walls lowers the water vapor diffusivity rate through wood. In this connection, many studies have also reported the great impact of the period of steaming on fluid flow (Schmidt 1982a, b;Kubinsky and Ifju 1974;Oltean et al 2007). The same results were observed in the steam-treated sapwood specimens in the present study.…”
Section: Diffusion Coefficientmentioning
confidence: 97%